2007
DOI: 10.1094/ats-2007-0911-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Biofungicides and Organic Fertilizer in the Management of Dollar Spot in Bermudagrass

Abstract: Dollar spot (DS), caused by Sclerotinia homoeocarpa F. T. Bennett, is a foliar disease of warm‐ and cool‐season grasses and occurs frequently throughout the growing season. A three‐year study was conducted to evaluate the efficacy of biofungicides for controlling DS of bermudagrass [Cynodon dactylon (L.) Pers. var. dactylon × C. transvaalensis Burtt‐Davy]. The biofungicides evaluated in this study were EcoGuard, TurfShield, and Actinovate SP. A slow‐release organic fertilizer was applied in conjunction with bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In the field experiment, dollar spot incidence varied from year to year. Environmental conditions, such as temperature and moisture, likely contributed to variation in dollar spot occurrence (Tomaso‐Peterson and Perry, 2007). In 2007, air temperatures were 9 to 18°C greater than in 2008 during the first 2 wk of the experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field experiment, dollar spot incidence varied from year to year. Environmental conditions, such as temperature and moisture, likely contributed to variation in dollar spot occurrence (Tomaso‐Peterson and Perry, 2007). In 2007, air temperatures were 9 to 18°C greater than in 2008 during the first 2 wk of the experiment.…”
Section: Discussionmentioning
confidence: 99%
“…For the in vitro study, treatments were arranged in a completely randomized design with eight replications, and the experiment was performed twice. Variances between the two experiments were homogeneous as determined by Levene's test, and therefore data were combined for ANOVA by PROC GLM (SAS Institute, 2008). Nonlinear regression of percentage inhibition of fungal mycelial growth in relation to diameter of the PDA plates was performed to determine the MSM dosage effect for the in vitro study 3 d after treatment (DAT).…”
Section: Discussionmentioning
confidence: 99%
“…Compacting snow is a practice that may lower the air temperature at the snow–soil interface below freezing and prevent certain snow molds from developing (Blunt and Tisserat, 2007). Additionally, the use of organic (Nelson and Craft, 1992; Liu et al, 1995; Boulter et al, 2002) and biological materials (Nelson, 1997; Hsiang et al, 1999; Tomaso‐Peterson and Perry, 2007) in turf systems have shown positive results for suppressing a variety of diseases, including some snow molds, in the Eastern United States and Canada. However, these materials have not shown similar or consistent effectiveness in the Western United States (Johnston and Golob, 2003; Blunt and Tisserat, 2007), and specifically little information on using cultural practices to manage snow molds from the Intermountain West is published.…”
Section: Useful Conversionsmentioning
confidence: 99%
“…During periods of high disease pressure, significant turf damage and unacceptable quality may result if left untreated with synthetic pesticides (3,4,6). Research is ongoing in the area of biostimulants, elicitors, and organic pesticides, (7,9,12) and will likely produce effective management practices. But to date, relatively few programs are applicable and available to golf course superintendents.…”
Section: Introductionmentioning
confidence: 99%